Resin prebaked anode and method for producing the same
Patent Information
- Application Number
- CN202511175130.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-08-21
AI Technical Summary
[0004]但是在研发该产品及其制备工艺时,如何实现树脂预备阳极的性能提升与工艺兼容性双赢,是亟需解决的问题
[0043] This application improves the softening point of thermoplastic phenolic resin by adjusting its weight-average molecular weight, making it consistent with or nearly identical to the softening point of asphalt, thus allowing for mixing using the same wet mixing step. This simplifies the preparation process of the resin prebaked anode, eliminating the need for additional mixing equipment or modifications to existing kneading processes. In this application, adding a small amount of thermoplastic phenolic resin significantly improves the performance of the obtained resin prebaked anode, such as its resistivity and compressive strength. Therefore, the method of this application fills the gap in current methods for improving the performance of resin prebaked anodes with low thermoplastic phenolic resin addition, demonstrating that high-performance resin prebaked anodes can be obtained even with low thermoplastic phenolic resin addition.
Smart Images

Figure QLYQS_1 
Figure BDA0005560102130000151 
Figure BDA0005560102130000161
Abstract
Description
Technical Field
[0001] This application relates to the technical field of prebaked anodes, specifically to a resin prebaked anode and its preparation method. Background Technology
[0002] Traditional prebaked anodes rely on coal tar pitch binders, which suffers from drawbacks such as high slag shedding rate, high resistivity, and insufficient environmental performance. To overcome these problems, a further improvement is made by using pure resin as a binder. Pure phenolic resin has high char residue and low pollution characteristics, significantly shortening the calcination time of the prepared resin anodes. Furthermore, the resin anodes prepared using this method exhibit excellent performance (increased compressive strength, reduced resistivity, and decreased air permeability, improving anode slag shedding performance). However, using pure resin as a binder requires significant modifications to the mixing equipment, the introduction of room-temperature molding processes, and a dedicated drying system due to the altered preparation process. This results in high implementation costs and a long development cycle for preparing resin prebaked anodes.
[0003] To meet the industry's urgent need for high-efficiency, low-carbon anodes, a smooth transition scheme for thermoplastic phenolic resin compounded with coal tar pitch is proposed. In this preparation process, only a phenolic resin silo needs to be added to the existing batching system, allowing for the production of resin-prebaked anodes using existing processes and equipment.
[0004] However, in the research and development of this product and its preparation process, how to achieve a win-win situation of improving the performance of the resin pre-anode and process compatibility is an urgent problem to be solved. Summary of the Invention
[0005] This application provides a resin prebaked anode and its preparation method.
[0006] This application involves the following:
[0007] 1. A prebaked resin anode, comprising the following raw materials in parts by weight:
[0008] 80-90 parts aggregate, 0.5-5 parts phenolic resin material, and 10-20 parts asphalt;
[0009] The phenolic resin material is a thermoplastic phenolic resin or a biomass resin.
[0010] The biomass resin is a mixture of thermoplastic phenolic resin and lignin.
[0011] The thermoplastic phenolic resin has a weight-average molecular weight of 4000-10000.
[0012] 2. The resin prebaked anode according to item 1, wherein the weight-average molecular weight of the thermoplastic phenolic resin is 4500-10000, preferably 4500-7000, and more preferably 4500-5500.
[0013] 3. The resin prebaked anode according to item 1 or 2, wherein the softening point of the thermoplastic phenolic resin is 100-115℃; preferably 102-107℃.
[0014] 4. The prebaked resin anode according to any one of items 1-4, wherein the thermoplastic phenolic resin has the following structure:
[0015] Wherein, n = 42-100, preferably, n = 42-66, more preferably, n = 42-55.
[0016] In some embodiments, when the weight-average molecular weight of the thermoplastic phenolic resin is 10,000, n = 91-100. In some embodiments, when the weight-average molecular weight of the thermoplastic phenolic resin is 5,000-6,000, n = 45-55. In some embodiments, when the weight-average molecular weight of the thermoplastic phenolic resin is 4,500, n = 42-43.
[0017] 5. The prebaked resin anode according to any one of items 1-4, wherein the biomass resin is a mixture of the thermoplastic phenolic resin and lignin at a mass ratio of 1:(0.1-0.5).
[0018] 6. The prebaked resin anode according to item 5, wherein the ash content of the lignin is <0.5wt%; and the phenolic hydroxyl content of the lignin is ≥1mol / kg;
[0019] Preferably, the potassium content in the lignin is ≤100ppm; the sodium content in the lignin is ≤100ppm.
[0020] Preferably, the sulfur content in the lignin is ≤2wt%.
[0021] 7. The prebaked resin anode according to any one of items 1-6, wherein, based on the weight of the aggregate, the aggregate comprises the following parts by weight of raw materials:
[0022] 20-20 parts of 0-1mm petroleum coke, 15-25 parts of 1-2mm petroleum coke, 25-35 parts of 2-4mm petroleum coke, 15-25 parts of 4-8mm petroleum coke, and 25-35 parts of 0.05-0.1mm fine petroleum coke.
[0023] 8. A method for preparing the resin prebaked anode according to any one of items 1-7, comprising the following steps:
[0024] Mixing: Mixing aggregates, phenolic resin materials and asphalt together;
[0025] Molding: The mixed materials are vibrated and shaped.
[0026] Calcination: The carbon block obtained by vibration molding is calcined, and then cooled to obtain the resin prebaked anode.
[0027] 9. The preparation method according to item 8, wherein the kneading comprises the following steps:
[0028] The aggregates are dry-mixed evenly, then the phenolic resin material and the asphalt are added, wet-mixed, and then cooled and discharged.
[0029] Alternatively, the mixing process may include the following steps: dry mixing the aggregate and the phenolic resin material until uniform, then adding the asphalt, wet mixing, and then cooling and discharging.
[0030] 10. The preparation method according to item 9, wherein the dry mixing temperature is 120-130°C, and / or the dry mixing time is 20-30 min;
[0031] And / or, the wet mixing temperature is 160-170℃, and / or, the wet mixing time is 30-40 min;
[0032] And / or, the discharge temperature is 160-170℃.
[0033] 11. The preparation method according to any one of items 8-10, wherein the molding temperature is 90-100°C; and / or the molding excitation force is 60-80t.
[0034] 12. The preparation method according to any one of items 8-11, wherein the calcination comprises the following steps:
[0035] Preheating stage: Increase the temperature to 280-320℃ at a heating rate of 25-35℃ / h;
[0036] Medium-temperature heating stage: slowly increase the temperature to 750-850℃ at a heating rate of 15-25℃ / h;
[0037] High-temperature roasting stage: Continue to heat to 1000-1250℃ at a heating rate of 30-40℃ / h, and hold at this temperature for 24-36h;
[0038] Cooling stage: Reduce the temperature to 180-220℃ at a rate of 15-30℃ / h, and then cool to room temperature;
[0039] Preferably, during the roasting process, the oxygen content in the roasting environment is controlled to be below 2%-3%.
[0040] In the above scheme, the main purpose of the preheating stage is to slowly remove the volatiles in the obtained product (resin anode); the main purpose of the medium-temperature heating stage is to promote the coking reaction of the binder and form a preliminary carbon skeleton structure; the main purpose of the high-temperature calcination stage is to complete the densification of the carbon material and improve the mechanical strength and conductivity of the anode; in the cooling stage, attention should be paid to avoiding anode cracking caused by thermal stress due to rapid cooling.
[0041] 13. The preparation method according to item 12, wherein the cooling method in the cooling stage is natural cooling, air blowing cooling, or slow cooling.
[0042] Invention Effects
[0043] This application improves the softening point of thermoplastic phenolic resin by adjusting its weight-average molecular weight, making it consistent with or nearly identical to the softening point of asphalt, thus allowing for mixing using the same wet mixing step. This simplifies the preparation process of the resin prebaked anode, eliminating the need for additional mixing equipment or modifications to existing kneading processes. In this application, adding a small amount of thermoplastic phenolic resin significantly improves the performance of the obtained resin prebaked anode, such as its resistivity and compressive strength. Therefore, the method of this application fills the gap in current methods for improving the performance of resin prebaked anodes with low thermoplastic phenolic resin addition, demonstrating that high-performance resin prebaked anodes can be obtained even with low thermoplastic phenolic resin addition. Detailed Implementation
[0044] It should be noted that certain terms are used in the specification and claims to refer to specific components. Those skilled in the art will understand that different terms may be used to refer to the same component. This specification and claims do not distinguish components based on differences in terminology, but rather on differences in their functions.
[0045] As used throughout the specification and claims, the terms "comprising" or "including" are open-ended and should be interpreted as "comprising but not limited to". The subsequent descriptions in the specification are preferred embodiments for carrying out this application; however, these descriptions are for the purpose of understanding the general principles of the specification and are not intended to limit the scope of this application. The scope of protection of this application shall be determined by the appended claims. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains.
[0046] It should be understood that the embodiments of this application described herein include embodiments that are "composed of" and / or "substantially composed of". References to values or parameters of "about" herein include (and describe) variations of that value or parameter itself. For example, a reference to "about X" includes a description of "X".
[0047] As used herein, references to “not” values or parameters generally refer to and describe “except” values or parameters. For example, “The method is not used to treat type X cancer” means that the method is used to treat cancers other than type X.
[0048] As used in this article, the term “approximately XY” has the same meaning as “approximately X to approximately Y”.
[0049] As used herein and in the appended claims, the singular forms “a / an” and “the” include the plural objects unless the context clearly indicates otherwise. It should also be noted that claims may be drafted to exclude any optional elements. Therefore, this statement is intended as a preliminary basis for the use of exclusive terms such as “only” or “merely” in conjunction with the description of the elements of the claim, or for the use of the limitation of “no”.
[0050] As used herein, the term "and / or" in words such as "A and / or B" is intended to include both A and B; A or B; A (alone); and B (alone). Similarly, as used herein, the term "and / or" in words such as "A, B and / or C" is intended to include each of the following embodiments: A, B and C; A, B or C; A or C; A or B; B or C; A and C; A and B; B and C; A (alone); B (alone); and C (alone).
[0051] As used in this article, "asphalt" is a product of deep processing of coal tar, mainly produced by further processing the residues after refining chemicals such as benzene, industrial naphthalene, and anthracene oil from high-temperature coal tar. During coal tar processing, the residue after distillation to remove liquid fractions is called coal tar pitch. Coal tar pitch is the main component of coal tar, accounting for approximately 50% to 60% of the total. It is generally believed that its main components are polycyclic aromatic hydrocarbons (PAHs) and their derivatives. The specific compound composition is very complex, and differences in raw coal type and processing technology can lead to variations in composition. At room temperature, coal tar pitch is a black, brittle, lustrous block with an unpleasant odor. It is easily combustible when melted and is toxic. Coal tar pitch has low temperature stability, good adhesion to mineral aggregates, poor climatic stability (large temperature variations), and contains a high amount of harmful components, especially carcinogenic PAHs such as benzo[a]pyrene, making it one of the main sources of such pollutants in the environment.
[0052] As used herein, "lignin" is intended to encompass any type of lignin, such as lignin derived from hardwoods, softwoods, or annular plants. Lignin may also be chemically modified. In some embodiments, lignin is purified or isolated.
[0053] This application provides a prebaked resin anode, which comprises the following raw materials in parts by weight:
[0054] 80-90 parts aggregate, 0.5-5 parts phenolic resin material, and 10-20 parts asphalt;
[0055] The phenolic resin material is a thermoplastic phenolic resin or a biomass resin.
[0056] The biomass resin is a mixture of thermoplastic phenolic resin and lignin.
[0057] The thermoplastic phenolic resin has a weight-average molecular weight of 4000-10000.
[0058] In this application, the applicant unexpectedly discovered that by adjusting the weight-average molecular weight of the thermoplastic phenolic resin to make its softening point within an appropriate range, it can be better mixed with asphalt to ensure uniform aggregate mixing. When this appropriate thermoplastic phenolic resin is added as a binder at a low amount (based on the total mass of the raw materials for preparing the resin prebaked anode, the amount of phenolic resin added is no more than about 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt%, 0.6 wt%, etc.), the performance of the obtained resin prebaked anode can be significantly improved.
[0059] In this application, the weight-average molecular weight of thermoplastic phenolic resin is determined by GPC (gel permeation chromatography), according to the following methods and conditions. In some embodiments, the specific steps of this detection method are as follows: The detection principle is to separate molecules of different sizes through a porous gel column and determine the molecular weight distribution based on the hydrodynamic volume difference. The detection steps are: I. Sample preparation. 1. The sample preparation solvent must be consistent with the instrument solvent system and be a good solvent for the polymer being tested. The sample must be dissolved in advance and fully dissolved; 2. The sample concentration is 2-5 mg / mL, not too concentrated or too dilute; 3. The prepared polymer solution must be clear and transparent, and filtered with a 0.22µm-0.45µm filter membrane before testing; 4. Use a 2mL chromatographic bottle, preferably with a cap with a pre-cut notch; 5. The solvent volume should not be too low, and the solvent level should be above 0.5m. II. Sample editing, testing, and data processing (check whether the solvent is sufficient and whether the temperature, pressure, etc. are normal before testing). 1. Check if the mobile phase is in circulation on the detector display. Before sampling, press shin+3 on the detector display to turn off circulation (remember to turn off circulation before sampling); 2. Sampling: In the sample queue interface, click "Edit Sample Plate," select the slot number, insert, and confirm. Edit the injection volume (10-50u, depending on the sample concentration), sample name, function (wide distribution sample injection), method group (GPC), and run time (40min). Leave other settings unchanged. After checking that the edited information is correct, submit the sample. In the pop-up window, fill in the sample group name, leave other information unchanged, and confirm submission. After sampling is complete and ensure that no other samples are being tested, press shin+3 on the detector display to turn on circulation (remember to turn on circulation when there is no testing); 3. Data processing: In the project browsing interface, find the channel, select the sample, right-click to view, open the file in the upper left corner, select the processing method for the latest date, click the integration icon at the top of the page (automatic integration is possible, or you can manually drag the integration), and after integration, click the quantification icon at the top. The corresponding M value will be displayed. Save the results in the upper left corner.
[0060] In this application, the softening point of the thermoplastic phenolic resin is tested using the ring and ball method. The softening point is determined by observing the temperature at which the molten resin or steel ball begins to contact the lower metal plate. In some embodiments, the test standard GB / T4507-2014 (Determination of Softening Point of Bituminous Pitch - Ring and Ball Method) is specifically referenced.
[0061] In this scheme, the applicant discovered through experiments that when the amount of phenolic resin material (specifically thermoplastic phenolic resin) added is controlled within the aforementioned range, the resulting resin prebaked anode exhibits significantly improved compressive strength (compressive strength not less than 39 MPa, even 42 MPa, 43 MPa, or even higher), reduced resistivity (as low as 55 Ω, even lower than 53 Ω, 51 Ω), and better bulk density. If the amount of phenolic resin material added exceeds 5 wt% (e.g., 6 wt%, 16 wt%, etc.), it will directly lead to a decrease in the performance of the resulting resin prebaked anode; for example, its resistivity will reach as high as 60 Ω, even 70 Ω, or even higher, and its compressive strength will significantly decrease to 38 MPa, 34 MPa, or even lower. The thermoplastic phenolic resin can be commercially available or obtained through preparation methods known to those skilled in the art.
[0062] In some implementations, the amount of aggregate added is any weight range within the range of 80-90 parts, 82-88 parts, 83-86 parts, or 80-90 parts, with reference to the total mass of the raw materials for preparing the resin prebaked anode; specifically, for example, any weight range within the range of 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 89 parts, 90 parts, or 80-90 parts. In some implementations, the amount of phenolic resin material added is any weight range within the range of 0.5-5 parts, 0.5-4 parts, 0.5-3 parts, 0.5-2 parts, 0.5-1 parts, 1-4 parts, 1-3 parts, 1-2 parts, or 0.5-5 parts, with reference to the total mass of the raw materials used in the preparation of the prebaked resin anode; specifically, for example, any weight range within the range of 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, or 0.5-5 parts. In some implementations, the amount of asphalt added is any weight range within the range of 10-20 parts, 12-18 parts, 13-17 parts, 14-16 parts, or 10-20 parts, with reference to the total mass of the raw materials used to prepare the prebaked resin anode; specifically, for example, any weight range within the range of 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, or 10-20 parts.
[0063] In some embodiments, the phenolic resin material is a thermoplastic phenolic resin. In some embodiments, the phenolic resin material is a biomass resin. In some embodiments, the biomass resin is a mixture of the thermoplastic phenolic resin and lignin at a mass ratio of 1:(0.1-0.5); for example, a mixture at any mass ratio within the range of 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, or 1:(0.1-0.5). The applicant has further discovered that replacing a small amount of thermoplastic phenolic resin with lignin, compared to selecting pure thermoplastic phenolic resin, can further improve the performance of the resulting resin prebaked anode. In some embodiments, the lignin is lignin prepared by an acid process. This application does not impose excessive restrictions on the plant source for preparing lignin; it can be, for example, reeds, corn cobs, corn stalks, wheat straw, or rice straw.
[0064] In some embodiments of this application, the weight-average molecular weight of the thermoplastic phenolic resin is any weight-average molecular weight range within the range of 4500-10000, 4500-7000, 6000-7000, 9000-10000, 4500-5500, or 4500-10000.
[0065] In some embodiments, the softening point of the thermoplastic phenolic resin is any softening point range within the range of 100-115°C, 105-115°C, 102-107°C, 115-120°C, 103-107°C, or 100-120°C.
[0066] In some embodiments, the thermoplastic phenolic resin has the following structure:
[0067] Where n = 42 - 100.
[0068] In some embodiments, the thermoplastic phenolic resin has the following structure:
[0069] Where n = 42 - 66.
[0070] In some embodiments, the thermoplastic phenolic resin has the following structure:
[0071] Where n = 42 - 55.
[0072] In some embodiments, the thermoplastic phenolic resin has the following structure:
[0073] Where n = 42 - 55;
[0074] Furthermore, the thermoplastic phenolic resin has a weight-average molecular weight of 4500-5500 and a softening point of 103-107℃.
[0075] In some embodiments, the ash content of the lignin is <0.5wt%, <0.4wt%, <0.3wt%, <0.2wt%, <0.1wt%, or <0.05wt%; for example, 0.5wt%, 0.45wt%, 0.4wt%, 0.35wt%, 0.3wt%, 0.25wt%, 0.2wt%, 0.15wt%, 0.1wt%, or 0.05wt%. In some embodiments, the phenolic hydroxyl content of the lignin is ≥1mol / kg, ≥2mol / kg, or ≥3mol / kg; for example, 1mol / kg, 1.5mol / kg, 2mol / kg, 2.5mol / kg, or 3mol / kg. In some embodiments, the phenolic hydroxyl content of the lignin is ≥1 mol / kg, preferably 1 mol / kg ≤ phenolic hydroxyl content ≤ 1.5 mol / kg; for example, 1.1 mol / kg, 1.2 mol / kg, 1.3 mol / kg, 1.4 mol / kg, 1.5 mol / kg; to provide sufficient active groups to ensure the normal progress of the reaction. In this application, an ash content higher than 0.5 wt% in the prebaked resin anode will affect the performance of the prebaked resin anode, thereby ensuring that the ash content in its lignin is lower than 0.5 wt%, to avoid the introduction of excessive impurities due to the addition of lignin.
[0076] In some embodiments, the potassium content in the lignin is ≤100ppm, ≤90ppm, ≤80ppm, ≤70ppm, ≤60ppm, ≤50ppm, ≤40ppm, ≤30ppm, or ≤20ppm; specifically, it is 100ppm, 95ppm, 85ppm, 75ppm, 65ppm, 55ppm, 45ppm, 35ppm, 25ppm, 15ppm, 10ppm, 5ppm, or 0ppm, or any content within the range thereof. In some embodiments, the sodium content in the lignin is ≤100ppm, ≤90ppm, ≤80ppm, ≤70ppm, ≤60ppm, ≤50ppm, ≤40ppm, ≤30ppm, or ≤20ppm; specifically, it is 100ppm, 95ppm, 85ppm, 75ppm, 65ppm, 55ppm, 45ppm, 35ppm, 25ppm, 15ppm, 10ppm, 5ppm, or 0ppm, or any content within the range thereof. In some embodiments, the sulfur content in the lignin is ≤2 wt%, more preferably below 0.5 wt%; for example, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 1 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, or 1.8 wt%. The addition of the aforementioned lignin prevents the introduction of excessive impurities, thereby ensuring that the prepared resin prebaked anode exhibits excellent performance.
[0077] In some embodiments, the lignin is prepared by an acid process. In some embodiments, the acid used in the acid process for preparing lignin is formic acid and / or acetic acid. In some embodiments, the lignin is any lignin prepared by an acid process (e.g., with formic acid and / or acetic acid), such as lignin prepared by an organic acid process according to the method in patent application number CN 201210570584.7. In some embodiments, the lignin is any commercially available lignin prepared by an acid process (e.g., with formic acid and / or acetic acid); for example, purchased from Jinan Shengquan Group Co., Ltd., product model SQDT-1.
[0078] In some embodiments, the aggregate comprises, by weight, the following parts of raw materials:
[0079] 0-1mm petroleum coke 10-20 parts, 1-2mm petroleum coke 15-25 parts, 2-4mm petroleum coke 25-35 parts, 4-8mm petroleum coke 15-25 parts, 0.05-0.1mm fine petroleum coke 25-35 parts.
[0080] In some embodiments, the aggregate comprises, by weight, the following parts by weight of raw material: 10-20 parts, 12-18 parts, 13-17 parts, 14-16 parts, or any part by weight of 0-1mm petroleum coke within the range of 10-20 parts; for example, it can be any part by weight of 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, or any part by weight within the range of 10-20 parts. In some embodiments, the aggregate comprises, by weight, the following parts by weight of raw material: 15-25 parts, 18-22 parts, 19-21 parts, or any weight range of 15-25 parts of 1-2mm petroleum coke; for example, it can be any weight range of 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 parts, or any weight range of 15-25 parts. In some embodiments, the aggregate comprises, by weight, the following parts by weight of raw material: 25-35 parts, 28-32 parts, 29-31 parts, or any weight range of 25-35 parts of 2-4mm petroleum coke; for example, it can be any weight range of 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 parts, or any weight range of 25-35 parts. In some embodiments, the aggregate comprises, by weight, the following parts by weight of raw material: 15-25 parts, 18-22 parts, 19-21 parts, or any part by weight of 4-8mm petroleum coke; for example, it can be any part by weight of 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 parts, or any part by weight of 15-25 parts. In some embodiments, the aggregate comprises, by weight, the following parts by weight of raw material: 25-35 parts, 28-32 parts, 29-31 parts, or any part by weight of 0.05-0.1mm petroleum coke; for example, it can be any part by weight of 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, or any part by weight of 25-35 parts.
[0081] The method for preparing the resin prebaked anode described in this application includes the following steps:
[0082] Mixing: Mixing aggregates, phenolic resin materials and asphalt together;
[0083] Molding: The mixed materials are vibrated and shaped.
[0084] Calcination: The carbon block obtained by vibration molding is calcined, and then cooled to obtain the resin prebaked anode.
[0085] In some implementations, the mixing process includes the following steps: dry mixing the aggregates until uniform, then adding the phenolic resin material and the asphalt, wet mixing, and then cooling and discharging.
[0086] In some embodiments, the mixing process includes the following steps: dry mixing the aggregate and the phenolic resin material, then adding the asphalt, wet mixing, and then cooling and discharging.
[0087] In this application, the mixing step does not require significant changes to the original production process due to the addition of phenolic resin material; it simply involves pre-mixing the phenolic resin material and asphalt, or pre-mixing the aggregate and phenolic resin material. Therefore, this process can achieve production with minimal equipment modifications, resulting in low costs for equipment improvements and process design.
[0088] In this application, the dry mixing is performed using methods known in the art, and the temperature and time of the dry mixing are well known to those skilled in the art. The dry mixing only needs to achieve uniform mixing of the aggregate and phenolic resin material. In some embodiments, the dry mixing temperature is any temperature range within the range of 120-130℃, 122-128℃, 123-127℃, 124-126℃, or 120-130℃; for example, it can be any temperature within the range of 120℃, 121℃, 122℃, 123℃, 124℃, 125℃, 126℃, 127℃, 128℃, 129℃, 130℃, or the range thereof. In some embodiments, the dry mixing time is 20-30 minutes; for example, it can be any time within the range of 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes, 30 minutes, or the range thereof. In some embodiments, the dry mixing temperature is 120-130°C and the dry mixing time is 20-30 minutes.
[0089] In this application, the wet mixing is a dry mixing process using methods known in the art. The temperature and time of the wet mixing are known to those skilled in the art, and the dry mixing only needs to achieve uniform mixing of the aggregate and phenolic resin material with the asphalt mixture. In some embodiments, the wet mixing temperature is any temperature range within the range of 160-170℃, 162-168℃, 163-167℃, 164-166℃, or 160-170℃; for example, it can be any temperature within the range of 160℃, 161℃, 162℃, 163℃, 164℃, 165℃, 166℃, 167℃, 168℃, 169℃, 170℃, or the range thereof. In some embodiments, the wet mixing time is 30-40 minutes; for example, it can be any time within the range of 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes, 40 minutes, or the range thereof. In some embodiments, the wet mixing temperature is 160-170°C, and the wet mixing time is 30-40 minutes.
[0090] In some embodiments, the discharge temperature is any temperature range within the range of 160-170℃, 162-168℃, 163-167℃, 164-166℃, or 160-170℃; for example, it can be any temperature within the range of 160℃, 161℃, 162℃, 163℃, 164℃, 165℃, 166℃, 167℃, 168℃, 169℃, 170℃, or 160℃.
[0091] In this application, there are no other special requirements for the vibration molding operation; it can be performed using methods and conditions known to those skilled in the art. In some embodiments, the vibration molding temperature is 90-100℃; for example, 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, 99℃, 100℃, or any temperature within the range thereof. In some embodiments, the vibration molding excitation force is 60-80t; for example, 60t, 61t, 62t, 63t, 64t, 65t, 66t, 67t, 68t, 69t, 70t, 71t, 72t, 73t, 74t, 75t, 76t, 77t, 78t, 79t, 80t, or any pressure within the range of 60-80t.
[0092] In some embodiments, the calcination includes the following steps: a preheating stage: heating to 280-320°C at a heating rate of 25-35°C / h; for example, heating rates of 25°C / h, 26°C / h, 27°C / h, 28°C / h, 29°C / h, 30°C / h, 31°C / h, 32°C / h, 33°C / h, 34°C / h, 35°C / h or any heating rate within the range thereof; for example, heating to 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C or any temperature within the range thereof.
[0093] In some embodiments, the calcination further includes the following steps: a medium-temperature heating stage: slowly heating to 750-850°C at a heating rate of 15-25°C / h; for example, heating rates of 15°C / h, 16°C / h, 17°C / h, 18°C / h, 19°C / h, 20°C / h, 21°C / h, 22°C / h, 23°C / h, 24°C / h, 25°C / h, or any heating rate within the range thereof; for example, heating to 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, or any temperature within the range thereof. In some embodiments, the medium-temperature heating stage is performed after the preheating stage.
[0094] In some embodiments, the calcination further includes the following steps: a high-temperature calcination stage: continuing to heat to 1000-1250℃ at a heating rate of 30-40℃ / h, and holding at this temperature for 24-36h; for example, heating rates of 30℃ / h, 31℃ / h, 32℃ / h, 33℃ / h, 34℃ / h, 35℃ / h, 36℃ / h, 37℃ / h, 38℃ / h, 39℃ / h, 40℃ / h, or any heating rate within the range thereof; for example, heating to 100℃ / h. 0℃, 1100℃, 1110℃, 1120℃, 1130℃, 1140℃, 1150℃, 1160℃, 1170℃, 1180℃, 1200℃, 1210℃, 1220℃, 1230℃, 1250℃, or any temperature within the range thereof; for example, holding at this temperature for 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, or any time within the range thereof. In some embodiments, the high-temperature roasting stage is performed after the intermediate-temperature heating stage.
[0095] In some embodiments, the calcination further includes the following steps: a cooling stage: reducing the temperature to 180-220°C at a cooling rate of 15-30°C / h, and then cooling to room temperature; for example, a heating rate of 15°C / h, 16°C / h, 17°C / h, 18°C / h, 19°C / h, 20°C / h, 21°C / h, 22°C / h, 23°C / h, 24°C / h, 25°C / h, 26°C / h, 27°C / h, 28°C / h, 29°C / h, 30°C / h, or any heating rate within the range thereof.
[0096] In some embodiments, during the roasting process, the oxygen content in the roasting environment is controlled to be below 3 vol.%; for example, the oxygen content in the roasting environment is controlled to be below 3 vol.%, 2.8 vol.%, 2.6 vol.%, 2.4 vol.%, 2.2 vol.%, 2 vol.%, 1.8 vol.%, 1.6 vol.%, 1.4 vol.%, 1.2 vol.%, 1 vol.%, 0.8 vol.%, 0.6 vol.%, 0.4 vol.%, 0.2 vol.%, 0.1 vol.%, or 0 vol.%.
[0097] Example
[0098] Specific embodiments of this application will now be described in more detail with reference to examples. It should be understood that this application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of this application and to fully convey the scope of this application to those skilled in the art.
[0099] The softening point test method for phenolic resin in this application is the ring and ball method. The temperature at which the heated and molten resin or steel ball first contacts the lower metal plate is the softening point temperature.
[0100] Methods for determining potassium and sodium elements in lignin: General rules for inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis JY / T 0567-2020.
[0101] The sulfur content was determined according to the enterprise standard of Jinan Shengquan Group Co., Ltd., "Determination of Sulfur in Lignin Binders by Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-AES)" Q / 370000JSQ054-2019.
[0102] The ash content testing method for the lignin used is as follows: refer to the enterprise standard of Jinan Shengquan Group Co., Ltd., Lignin Binder Q / 370000JSQ 005-2025.
[0103] Example 1
[0104] Preparation method of resin prebaked anode:
[0105] (a) Aggregate: Weigh out 15 parts of 0-1mm petroleum coke, 20 parts of 1-2mm petroleum coke, 30 parts of 2-4mm petroleum coke, 20 parts of 4-8mm petroleum coke, and 30 parts of 180-mesh fine petroleum coke according to the following proportions and mix them evenly in a mixer to obtain aggregate.
[0106] (b) Thermoplastic phenolic resin: Phenolic resin with a weight average molecular weight of 4500-5500 and a softening point of 105±2℃.
[0107] The structural formula of thermoplastic phenolic resin is shown below:
[0108] Where n = 42 - 55.
[0109] The preparation method of this thermoplastic phenolic resin is as follows:
[0110] Phenol and formaldehyde were added to a reaction vessel at a molar ratio of 1:0.8, followed by the addition of oxalic acid as a catalyst (1% of the phenol mass). The mixture was stirred and heated to 70°C and maintained at this temperature for 1 hour. Then, the temperature was raised to 100°C and refluxed for 4 hours. After the reaction was completed, distillation and dehydration were initiated. The temperature was raised to 110°C and stabilized for 1.5 hours before further heating. Finally, phenol was removed under vacuum at 150°C–160°C. The material was discharged after 1 hour of phenol removal at a negative pressure of 0.97 MPa.
[0111] (c) Mixing: Add 84 parts by weight of the aggregate obtained in step (a) to the mixing equipment and dry mix for 25 minutes to bring the dry material temperature to 120-130℃. Then add 15 parts by weight of asphalt and 1 part by weight of thermoplastic phenolic resin from step (b) (i.e., aggregate: asphalt: thermoplastic phenolic resin = 84:15:1, weight ratio) and wet mix for 40 minutes. The final paste discharge temperature is between 160-170℃.
[0112] (d) Place the mixed material from step (c) into a specific mold, with the mold temperature controlled at 95±2℃, and form it using a vibration molding machine with a vibration force of 60 tons.
[0113] (e) The formed charcoal blocks are placed in a high-temperature roasting furnace for heat treatment:
[0114] Preheating stage: The temperature is increased to 300℃ at a heating rate of 30℃ / h to slowly remove the volatiles in the anode, while the thermoplastic phenolic resin powder begins to carbonize initially.
[0115] Medium-temperature heating stage: The temperature is slowly increased to 800℃ at a heating rate of 20℃ / h to promote the coking reaction of the binder and form a preliminary carbon skeleton structure.
[0116] High-temperature calcination stage: The temperature is increased to 1100℃ at a rate of 35℃ / h and held at this temperature for 30h to complete the densification of the carbon material and improve the mechanical strength and conductivity of the anode.
[0117] Cooling stage: The temperature is reduced to 200℃ at a rate of 20℃ / h, followed by natural cooling to room temperature to avoid thermal stress caused by rapid cooling, which could lead to anode cracking. The furnace atmosphere must be strictly controlled throughout the roasting process to ensure the oxygen content is below 3% (vol.%) to prevent oxidation of the anode.
[0118] Example 2
[0119] The difference between this embodiment and Embodiment 1 is that the order of adding materials in step (c) is different, as follows: 84 parts by weight of aggregate obtained in step (a) and 1 part by weight of thermoplastic phenolic resin powder obtained in step (b) are added to the mixing equipment and dry-mixed for 25 minutes to make the dry material temperature 120-130℃. Then, 15 parts by weight of asphalt are added and wet-mixed for 40 minutes. The final paste discharge temperature is between 160-170℃.
[0120] Comparative Example 1
[0121] The difference between this comparative example and Example 1 lies in the different proportions of aggregate, asphalt, and thermoplastic phenolic resin added during the kneading process in step (c). Specifically, the proportions are: aggregate: 84 parts by weight, asphalt: 10 parts by weight, and thermoplastic phenolic resin: 6 parts by weight (i.e., aggregate: asphalt: thermoplastic phenolic resin = 84:10:6, by weight). Everything else is the same as in Example 1.
[0122] Comparative Example 2
[0123] The difference between this comparative example and Example 1 lies in the different amounts of aggregate, asphalt, and thermoplastic phenolic resin added during the kneading process in step (c). Specifically, the aggregate content is 84 parts by weight, the asphalt content is 0 parts by weight, and the thermoplastic phenolic resin content is 16 parts by weight (i.e., aggregate:asphalt:thermoplastic phenolic resin = 84:0:16, by weight). Everything else is the same as in Example 1.
[0124] Example 3
[0125] The difference between this embodiment and Embodiment 1 lies in the amount of aggregate, asphalt, and thermoplastic phenolic resin added in the kneading process of step (c). Specifically, the aggregate content is 84 parts by weight, the asphalt content is 14.5 parts by weight, and the thermoplastic phenolic resin content is 1.5 parts by weight (i.e., aggregate:asphalt:thermoplastic phenolic resin = 84:14.5:1.5, by weight). Everything else is the same as in Embodiment 1.
[0126] Comparative Example 3
[0127] The difference between this comparative example and Example 1 lies in the different amounts of aggregate, asphalt, and thermoplastic phenolic resin added during the kneading process in step (c). Specifically, the amounts are: aggregate: 85 parts by weight, asphalt: 15 parts by weight, and thermoplastic phenolic resin: 0 parts by weight (i.e., aggregate: asphalt: thermoplastic phenolic resin = 85:15:0, weight ratio). Everything else is the same as in Example 1.
[0128] Example 4
[0129] The difference between this embodiment and Embodiment 1 lies in the amount of aggregate, asphalt, and thermoplastic phenolic resin added in the kneading process of step (c). Specifically, the aggregate content is 83.5 parts by weight, the asphalt content is 15 parts by weight, and the thermoplastic phenolic resin content is 1.5 parts by weight (i.e., aggregate:asphalt:thermoplastic phenolic resin = 83.5:15:1.5, by weight). Everything else is the same as in Embodiment 1.
[0130] The parameters that have changed in the implementation schemes of Examples 1 to 4 and Comparative Examples 1 to 3 are summarized in Table 1.
[0131] Table 1
[0132]
[0133]
[0134] Performance testing:
[0135] Prebaked resin anodes with no cracks or gaps and rounded shapes were selected. The resistivity, bulk density and withstand voltage of the obtained resin anodes were tested according to the test methods in YS / T63.2-2024, YS / T 63.7-2024 and YS / T 63.15-2024 respectively. The specific results are shown in Table 2.
[0136] Table 2
[0137] Example 1 55 1.61 42 Example 2 57 1.60 41 Comparative Example 1 65 1.56 37 Comparative Example 2 70 1.55 34 Example 3 61 1.58 39 Comparative Example 3 60 1.57 38 Example 4 62 1.59 40
[0138] There is a significant positive correlation between the softening point and the weight-average molecular weight of thermoplastic phenolic resins. Generally, the higher the molecular weight, the higher the softening point. The following implementation schemes investigated the effect of preparing resin prebaked anodes with thermoplastic phenolic resins of different molecular weights and softening points on the performance of the resulting resin prebaked anodes.
[0139] Example 5
[0140] The difference between this embodiment and Embodiment 1 lies in the weight-average molecular weight and softening point of the thermoplastic phenolic resin. In this embodiment, the weight-average molecular weight of the thermoplastic phenolic resin is 6000-7000, and the softening point is 105-115℃.
[0141] The structural formula of thermoplastic phenolic resin is shown below:
[0142] Where n = 54 - 67.
[0143] The preparation method of this thermoplastic phenolic resin is as follows:
[0144] Phenol and formaldehyde were added to a reactor at a molar ratio of 1:0.81, followed by the addition of oxalic acid as a catalyst (1% of the phenol mass). The mixture was stirred and heated to 70°C and maintained at this temperature for 1 hour. Then, the temperature was raised to 100°C and refluxed for 5 hours. After the reaction was completed, distillation and dehydration were initiated. The temperature was raised to 110°C and stabilized for 1.5 hours before further heating. Finally, phenol was removed under vacuum at 150°C–160°C. The material was discharged after 1 hour of phenol removal at a negative pressure of 0.97 MPa.
[0145] Example 6
[0146] The difference between this embodiment and Embodiment 1 lies in the weight-average molecular weight and softening point of the thermoplastic phenolic resin. In this embodiment, the weight-average molecular weight of the thermoplastic phenolic resin is 9000-10000, and the softening point is 115-120℃.
[0147] The structural formula of thermoplastic phenolic resin is shown below:
[0148] Where n = 82 - 100.
[0149] The preparation method of this thermoplastic phenolic resin is as follows:
[0150] Phenol and formaldehyde were added to a reactor at a molar ratio of 1:0.82, followed by the addition of oxalic acid as a catalyst (1.1% of the phenol mass). The mixture was stirred and heated to 70°C and maintained at this temperature for 1 hour. Then, the temperature was raised to 100°C and refluxed for 5.5 hours. After the reaction was completed, distillation and dehydration were initiated. The temperature was raised to 110°C and stabilized for 1.5 hours before further heating. Finally, phenol was removed under vacuum at 150°C–160°C. The material was discharged after 1.5 hours of dephenolization at a negative pressure of 0.97 MPa.
[0151] Comparative Example 4
[0152] The difference between this embodiment and Embodiment 1 lies in the weight-average molecular weight and softening point of the thermoplastic phenolic resin. In this embodiment, the weight-average molecular weight of the thermoplastic phenolic resin is 500-1000, and the softening point is 70-80℃.
[0153] The structural formula of thermoplastic phenolic resin is shown below:
[0154] Where n = 4 - 10.
[0155] The preparation method of this thermoplastic phenolic resin is as follows:
[0156] Phenol and formaldehyde were added to the reactor at a molar ratio of 1:0.75. Then, oxalic acid, a catalyst, was added, with the mass of oxalic acid being 0.8% of that of phenol. The mixture was stirred and heated to 70°C and maintained at this temperature for 1 hour. The temperature was then raised to 100°C and refluxed for 3 hours. After the reaction was completed, distillation and dehydration were started. The temperature was raised to 120°C and stabilized for 1 hour before being raised again. When the temperature reached 150°C to 160°C, phenol was removed under vacuum. When the negative pressure reached 0.97 MPa, the phenol was removed for 0.5 hours and the mixture was discharged.
[0157] Comparative Example 5
[0158] The difference between this embodiment and Embodiment 1 lies in the weight-average molecular weight and softening point of the thermoplastic phenolic resin. In this embodiment, the weight-average molecular weight of the thermoplastic phenolic resin is 2500-3500, and the softening point is 80-90℃.
[0159] The structural formula of thermoplastic phenolic resin is shown below:
[0160] Where n = 22 - 31.
[0161] The preparation method of this thermoplastic phenolic resin is as follows:
[0162] Phenol and formaldehyde were added to the reactor at a molar ratio of 1:0.78. Then, oxalic acid, a catalyst, was added, with the mass of oxalic acid being 0.9% of that of phenol. The mixture was stirred and heated to 70°C and maintained at this temperature for 1 hour. Then, the temperature was raised to 100°C and refluxed for 3.5 hours. After the reaction was completed, distillation and dehydration were started. The temperature was raised to 120°C and stabilized for 1 hour before being raised again. When the temperature reached 150°C to 160°C, phenol was removed under vacuum. When the negative pressure reached 0.97 MPa, phenol was removed for 1 hour before the material was discharged.
[0163] Comparative Example 6
[0164] The difference between this embodiment and Embodiment 1 lies in the weight-average molecular weight of the thermoplastic phenolic resin. In this embodiment, the weight-average molecular weight of the thermoplastic phenolic resin is 15,000-16,000, and the softening point is >120℃.
[0165] The structural formula of thermoplastic phenolic resin is shown below:
[0166] Where n = 139 - 148.
[0167] The preparation method of this thermoplastic phenolic resin is as follows:
[0168] Phenol and formaldehyde were added to the reactor at a molar ratio of 1:0.85. Then, oxalic acid, a catalyst, was added at a mass of 1.2% of the phenol content. The mixture was stirred and heated to 70°C and maintained at this temperature for 1 hour. The temperature was then raised to 100°C and refluxed for 6 hours. After the reaction was completed, distillation and dehydration were started. The temperature was raised to 110°C and stabilized for 1.5 hours before the temperature was raised further. Finally, the phenol was removed under vacuum at 150°C to 160°C. When the negative pressure reached 0.97 MPa, the phenol was removed for 2 hours before the material was discharged.
[0169] The parameters that have changed in the implementation schemes of Examples 1, 5 to 6, and Comparative Examples 4 to 6 are summarized in Table 3.
[0170] Table 3
[0171] Example 1 4500-5500 103-107℃ Example 5 6000-7000 105-115℃ Example 6 9000-10000 115-120℃ Comparative Example 4 500-1000 70-80℃ Comparative Example 5 2500-3500 80-90℃ Comparative Example 6 15000-16000 >120℃
[0172] Performance testing:
[0173] Prebaked resin anodes with no cracks or gaps and a rounded shape were selected and their resistivity, bulk density, and withstand voltage were tested according to the test methods in YS / T63.2-2024, YS / T 63.7-2024, and YS / T 63.15-2024. The specific results are shown in Table 4.
[0174] Table 4
[0175]
[0176] Example 7
[0177] The difference between this embodiment and Embodiment 1 is that the phenolic resin material is a biomass resin; that is, an equal part by weight of biomass resin replaces the phenolic resin. The other steps are the same as in Embodiment 1.
[0178] Specifically: Biomass resin is made by mixing thermoplastic phenolic resin and lignin in a weight ratio of 1:0.2; the lignin is dried to a moisture content of less than 2 wt.% before mixing; during mixing, the two materials are fed into the mixer in the above ratio, the speed is set to 35-40 rpm, and the mixing time is 25-30 minutes.
[0179] The lignin was purchased from Jinan Shengquan Group Co., Ltd., product model SQDT-1, batch number A24B160007. The lignin has an ash content of <0.5wt% and a phenolic hydroxyl content of 1.25mol / kg.
[0180] Comparative Example 8
[0181] In this embodiment, the phenolic resin material is a biomass resin; that is, an equal part by weight of biomass resin replaces the phenolic resin.
[0182] The difference between this embodiment and Embodiment 7 is that the biomass resin is a mixture of thermoplastic phenolic resin and lignin in a weight ratio of 1:0.05, while the rest is the same as in Embodiment 7.
[0183] Comparative Example 9
[0184] In this embodiment, the phenolic resin material is a biomass resin; that is, an equal part by weight of biomass resin replaces the phenolic resin.
[0185] The difference between this embodiment and Embodiment 7 is that the biomass resin is a mixture of thermoplastic phenolic resin and lignin in a 1:1 weight ratio, while the rest is the same as in Embodiment 7.
[0186] Comparative Example 10
[0187] In this embodiment, the phenolic resin material is a biomass resin; that is, an equal part by weight of biomass resin replaces the phenolic resin.
[0188] The difference between this embodiment and Embodiment 7 is that the lignin in the biomass resin is prepared using the traditional Kraft alkaline method; otherwise, it is the same as in Embodiment 7. The lignin prepared using the traditional Kraft alkaline method was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., product number HXKJ2023.
[0189] Its preparation is briefly described as follows:
[0190] The preparation of alkali lignin is mainly achieved through the alkali pulping process, and the specific steps are as follows:
[0191] Raw material processing
[0192] Plant fiber raw materials (such as wood) are treated with alkaline solutions such as sodium hydroxide, which dissolve lignin in the liquid phase while cellulose remains as a solid.
[0193] Separation and Concentration
[0194] The dissolved lignin is separated by filtration to obtain pulping black liquor. The black liquor is then concentrated to a concentration of 40-47% by an evaporation and concentration process (such as five-effect countercurrent evaporation) to reduce energy consumption and avoid scaling.
[0195] Drying and shaping
[0196] The concentrated black liquor is then spray-dried into powdered alkali lignin. This method effectively removes moisture and maintains the uniformity of the product particles.
[0197] Modified applications
[0198] Some processes involve adding acidic substances to adjust the pH value and promote lignin precipitation (such as acid precipitation), but this has problems such as high cost and high equipment requirements.
[0199] Performance testing:
[0200] Prebaked resin anodes with no cracks or gaps and a rounded shape were selected and their resistivity, bulk density, and withstand voltage were tested according to the test methods in YS / T63.2-2024, YS / T 63.7-2024, and YS / T 63.15-2024. The specific results are shown in Table 5.
[0201] Table 5
[0202]
[0203]
[0204] The description in this disclosure is provided for illustrative and descriptive purposes only and is not intended to be exhaustive or to limit the disclosure to its forms. Many modifications and variations will be apparent to those skilled in the art. The embodiments were chosen and described in order to better illustrate the principles and practical application of this disclosure and to enable those skilled in the art to understand this disclosure and to design various embodiments with various modifications suitable for a particular purpose.
Claims
1. A prebaked resin anode, comprising the following raw materials in parts by weight: 80-90 parts aggregate, 0.5-5 parts phenolic resin material, and 10-20 parts asphalt; in, The phenolic resin material is a thermoplastic phenolic resin or a biomass resin; The biomass resin is a mixture of thermoplastic phenolic resin and lignin. The thermoplastic phenolic resin has a weight-average molecular weight of 4000-10000.
2. The resin prebaked anode according to claim 1, wherein, The weight-average molecular weight of the thermoplastic phenolic resin is 4500-10000. And / or, wherein the softening point of the thermoplastic phenolic resin is 100-115℃.
3. The resin prebaked anode according to claim 1, wherein, The weight-average molecular weight of the thermoplastic phenolic resin is 4500-7000.
4. The resin prebaked anode according to claim 1, wherein, The thermoplastic phenolic resin has a weight-average molecular weight of 4500-5500.
5. The resin prebaked anode according to claim 1, wherein, The softening point of the thermoplastic phenolic resin is 102-107℃.
6. The resin prebaked anode according to any one of claims 1-5, wherein, The thermoplastic phenolic resin has the following structure: , where n = 42 - 100.
7. The prebaked resin anode according to claim 6, wherein, n=42-66。 8. The resin prebaked anode according to claim 6, wherein, n=42-55。 9. The resin prebaked anode according to claim 1, wherein, The biomass resin is obtained by mixing the thermoplastic phenolic resin and lignin at a mass ratio of 1:(0.1-0.5).
10. The resin prebaked anode according to claim 7, wherein, The ash content of the lignin is <0.5wt%; the phenolic hydroxyl content of the lignin is ≥1mol / kg.
11. The resin prebaked anode according to claim 1, wherein, Based on the weight of the aggregate, the aggregate comprises the following parts by weight of raw materials: 20-20 parts of 0-1mm petroleum coke, 15-25 parts of 1-2mm petroleum coke, 25-35 parts of 2-4mm petroleum coke, 15-25 parts of 4-8mm petroleum coke, and 25-35 parts of 0.05-0.1mm fine petroleum coke.
12. A method for preparing the resin prebaked anode according to any one of claims 1-11, comprising the following steps: Mixing: Mixing aggregates, phenolic resin materials and asphalt together; Molding: The mixed materials are vibrated and shaped. Calcination: The carbon block obtained by vibration molding is calcined, and then cooled to obtain the resin prebaked anode.
13. The preparation method according to claim 12, wherein, The kneading process includes the following steps: The aggregates are dry-mixed evenly, then the phenolic resin material and the asphalt are added, wet-mixed, and then cooled and discharged. Alternatively, the mixing process may include the following steps: dry mixing the aggregate and the phenolic resin material until uniform, then adding the asphalt, wet mixing, and then cooling and discharging.
14. The preparation method according to claim 13, wherein, The dry mixing temperature is 120-130℃, and / or the dry mixing time is 20-30 min; And / or, the wet mixing temperature is 160-170℃, and / or, the wet mixing time is 30-40 min; And / or, the discharge temperature is 160-170℃; And / or, wherein the molding temperature is 90-100℃; and / or, the molding excitation force is 60-80t.
15. The preparation method according to any one of claims 12-14, wherein, The roasting process includes the following steps: Preheating stage: Increase the temperature to 280-320℃ at a heating rate of 25-35℃ / h; Medium-temperature heating stage: slowly increase the temperature to 750-850℃ at a heating rate of 15-25℃ / h; High-temperature roasting stage: Continue to heat to 1000-1250℃ at a heating rate of 30-40℃ / h, and hold at this temperature for 24-36h; Cooling stage: Reduce the temperature to 180-220℃ at a rate of 15-30℃ / h, and then cool to room temperature.
16. The preparation method according to claim 15, wherein, During the roasting process, the oxygen content in the roasting environment is controlled to be below 2-3 vol.%.
Citation Information
Patent Citations
Comprehensive utilization technology of biomass raw materials
CN103030815A
Low-resistivity anode carbon block for aluminum electrolysis and preparation method thereof
CN113336552A
High molecular weight thermoplastic phenolic resin with narrow molecular weight distribution and preparation method thereof
CN118878764A